Molecular mechanisms of vascular calcification in diabetes mellitus: insights from human aortic smooth muscle cells, a systematic review - Weningtyas, Anditri; Rohman, Mohammad Saifur; Chomsy, Indah Nur; Hose, Victor Alvianoes Guterez; Riza, Mochamad Faishal; Purbaningroom, Dian Laila; Rudijanto, Achmad; Nugrahenny, Dian (Universitas Brawijaya, 2026)
Background: Vascular calcification is a significant contributor to cardiovascular complications in diabetes mellitus (DM), particularly affecting the prognosis of patients. Objectives: To conduct a comprehensive analysis of the molecular mechanisms underlying vascular calcification in DM, with a focus on insights from human aortic smooth muscle cells (HASMCs). Methods: The search was conducted following the PRISMA guidelines, utilizing databases such as MEDLINE/PubMed, Science Direct, and Google Scholar. The search focused on articles published within the last 5 years that discussed the molecular mechanisms of vascular calcification in DM, specifically in HASMCs. Results: Five selected reviews were found in a total of 637 articles. DM significantly accelerates vascular calcification in HASMCs through the upregulation of osteogenic markers and activation of the Wnt/β-catenin signaling pathway. Other identified mechanisms include inflammation, ferroptosis, and endothelial dysfunction, contributing to the complex interplay of factors that drive vascular calcification in diabetic patients. Conclusion: It is concluded that DM significantly accelerates vascular calcification in enhanced expression of osteogenic markers and activation of the Wnt/β-catenin signaling pathway in human aortic smooth muscle cells. Patients with diabetes are more likely to have cardiovascular issues as a result of this pathological process.